Designing for change through “reflecting and doing”: the CGIAR Community of Practice on Gender- Transformative Research Methodologies - López, Diana E.; Bailey, Arwen; Farnworth, Cathy Rozel; Rietveld, Anne; Gartaula, Hom Nath (Frontiers Media, 2023)
Gender-transformative change requires a commitment from everyone involved in agricultural research for development (AR4D) including organizations at international and national level, individual researchers and practitioners, farmers, development agencies, policy-makers and consumers, to transform the existing values, practices and priorities that (re)produce and perpetuate gender biases and inequities in agrifood systems. However, the adoption of a gender transformative agenda can be challenging, especially for AR4D organizations whose primary focus is not necessarily the attainment of gender equality. This paper looks at a collective, bottom-up, transformative effort within the AR4D organization of CGIAR. It advances the emerging CGIAR Community of Practice on Gender Transformative Research Methodologies (GTRM-CoP) as a case study to explore the potential of CoPs as social learning systems that create the conditions for transformation-oriented learning. Driven by an ethos of reflecting and doing anchored in critical and feminist principles and social learning praxis, the GTRM-CoP aims to be a safe space to spur reflexivity, creativity and collaboration to support existing work on gender transformation in CGIAR while re-imagining how gender in AR4D is conceptualized, negotiated and advanced. The paper focuses on the process leading to the development of the CoP, that is, designing for change, which is crucial for sustained transformation.